ABRIGO TEMPORÁRIO APLICÁVEL ÀS ZONAS BIOCLIMÁTICAS BRASILEIRAS DE MAIOR OCORRÊNCIA DE DESASTRES NATURAIS: APRESENTAÇÃO DA PROPOSTA E ANÁLISE DO DESEMPENHO TÉRMICO - Alves, Marcos Fábio Guimarães; Vilela, Fábio Barbosa; Cordeiro, Henrique Gonçalves; Andrade, Rafael Carvalho; Oliveira, Raquel Diniz; Hirashima, Simone Queiroz da Silveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
There is a growing need for temporary shelters in Brazil due to high occurrence of hydrological disasters such as inundations, floods and flurries. The authors aimed at developing an emergency and temporary shelter (from 6 up to 18 months) to be used in the Brazilian bioclimatic zones 1, 2, 3, 5 and 8. The shelter design was guided by principles of bioclimatic architecture and sustainable construction encompassing guidelines such as modularity, low cost, ease of transportation, speed and simplicity of construction and maintenance. This paper presents a proposal for the shelter and an evaluation of its building thermal performance envelopment considering Brazilian Standards ABNT-NB15.220(2005) and ABNT-NBR15.575(2013). Although the shelter proposal initially failed to meet the standards criteria, after enlarging ventilation areas and adopting water tanks internally in the vertical walls, the project is proper for all bioclimatic zones considered. In conclusion, the simultaneous compliance with the building thermal performance requirements of several bioclimatic zones is possible and relevant, mainly in contexts of climatic variability as large as the Brazilian one.